2005
DOI: 10.1111/j.1440-1819.2005.01392.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between insight and medication adherence in outpatients with schizophrenia and bipolar disorder: Prospective study

Abstract: The aim of the present study was to explore the associations between insight and medication adherence at index interview and at 1-year follow-up interview in bipolar and schizophrenic outpatients. The Schedule for Assessment of Insight (SAI) and its expanded version (SAI-E) were used to provide a baseline insight score for 65 bipolar subjects and 74 schizophrenic subjects considered to be in remission or to have minimal psychopathology. Medication adherence of subjects was assessed at index interview and at 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
65
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 32 publications
(44 reference statements)
4
65
1
2
Order By: Relevance
“…Indeed, only one interview-based measure, the SAI-E, has been found to correlate with treatment adherence cross-sectionally and to predict treatment adherence at 1-year followup among people with bipolar disorder (Yen et al, 2005). We can not identify a single selfreport measure of treatment attitudes that has been predictive of treatment engagement and symptoms within bipolar disorder.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Indeed, only one interview-based measure, the SAI-E, has been found to correlate with treatment adherence cross-sectionally and to predict treatment adherence at 1-year followup among people with bipolar disorder (Yen et al, 2005). We can not identify a single selfreport measure of treatment attitudes that has been predictive of treatment engagement and symptoms within bipolar disorder.…”
mentioning
confidence: 70%
“…It remains possible that in a sample with fewer lifetime episodes of illness, other treatment attitudes, including scores on the Insight subscale, would be more predictive; our study is limited by the reliance on a sample with quite severe histories. Most important, one subscale of the TAQ, Nonbiological Attributions, predicted lithium levels and depressive symptoms over time.Given that we can identify only one interviewed-based measure of treatment attitudes that predicted lithium levels over time within bipolar disorder (Yen et al, 2005), our findings that a brief self-report scale can help predict study drop-out, medication levels, and depressive symptoms appear to have important clinical implications. That is, understanding treatment attitudes should help identify patients at risk for relapse and treatment disengagement, but should also provide windows into defining better interventions.…”
mentioning
confidence: 99%
“…Although the underlying mechanism causing lack of insight is unknown, numerous studies have shown that severity of clinical symptoms is strongly associated with lack of insight [17][18][19][20]. Additionally, lack of insight has been found in several studies to be directly related to poor medication adherence [21][22][23][24], and one author suggested that appreciating the need for treatment was one of the three central features of insight [25].…”
Section: Introductionmentioning
confidence: 96%
“…Uma menor ou maior consciência quanto a estar doente ou apresentar sintomas ou algum prejuízo psicossocial pode influenciar significativamente a evolução da própria doença, afetando no mínimo a adesão ao tratamento [2][3][4][5] . O insight é investigado em pacientes neurológicos desde o final do século XIX, passando a ser pesquisado em pacientes psiquiátricos apenas mais recentemente.…”
Section: Introductionunclassified
“…Por outro lado, a associação entre outros fatores sociodemográfi-cos, como gênero ou idade, e o insight parece não ter sido amplamente estudada. Também se torna importante discutir outras possíveis consequências do comprometimento do insight em bipolares, além do prejuízo da adesão medicamentosa [2][3][4][5] . A possível influência do insight sobre a qualidade de vida ou sobre a evolução da doença, incluindo tentativas de suicídio, precisa ser mais bem compreendida.…”
Section: Introductionunclassified